Melanoxylonin A-G, neoflavonoids from the heartwood of Dalbergia melanoxylon and their cardioprotective effects. (September 2021) - Liu, Yang; Shu, Ji-Cheng; Wang, Meng-Fei; Xu, Zhang-Jun; Yang, Li; Meng, Xiao-Wei; Duan, Wen-Bing; Zhang, Ni; Shao, Feng; Liu, Rong-Hua; Chen, Lan-Ying
Abstract: Seven undescribed neoflavonoids, named melanoxylonins A-G, were isolated from the heartwood of Dalbergia melanoxylon, and all the non-toxic isolates were evaluated for their cardioprotective effect against ischemia/reoxygenation (I/R) injury in H9c2 cells. Of these, melanoxylonin A-D containing the 8-OH group showed better potent cardioprotective effects than the other four congeners. Molecular docking studies confirmed the capacity of melanoxylonin D to interact with the myeloperoxidase (MPO) protein. These results indicated that the potential cardioprotective effects of melanoxylonin D in H9c2 cells with I/R injury may be imparted through suppression of MPO. These results may provide a new medicinal usage of D. melanoxylon. Graphical abstract: Image 1 Highlights: Seven undescribed and five known neoflavoinds were isolated. Melanoxylonin A-D containing the 8-OH group showed better potent cardioprotective effects. This is the first time to discuss the structure-activity relationships of neoflavoinds.